Procyanidin B2 enhances anti-inflammatory responses of periodontal ligament cells by inhibiting the dominant negative pro-inflammatory isoforms of peroxisome proliferator-activated receptor γ - Tadahiro Yamamoto; Hang Yuan; Shigeki Suzuki; Eiji Nemoto; Masahiro Saito; Satoru Yamada (Elsevier, 2024)
Background/purpose: Periodontal breakdown in periodontitis is exacerbated by pro-inflammatory responses of periodontal stromal cells such as periodontal ligament fibroblasts (PDLFs). Procyanidin B2 (PB2) is a ligand of the peroxisome proliferator-activated receptor (PPARγ). Herein, we investigated the expression of PPARγ isoforms in PDLFs and periodontal tissue, and examined the effects of PB2 on PPARγ isoform-dependent antiinflammatory responses. Materials and methods: PPARγ isoforms were examined by PCR. PPARγ isoform-dependent inflammatory functions and anti-inflammatory effects of PB2 in PDLFs were evaluated based on IL-6 expression. Co-immunoprecipitation analysis of fixed chromatin-tethered protein (CoIPfctp) was conducted to investigate the association of each PPARγ isoform with the NF-κB-transcriptional complex. The effects of PB2 on periodontitis progression were evaluated using a ligature-induced murine periodontitis model. Results: Three isoforms of PPARγ were expressed in PDLFs and periodontal tissues, consisting of the main full-length isoform (PPARγ) and two dominant negative isoforms that lack the ligand binding domain, namely the ubiquitously-expressed isoform (PPARγ-UBI) and unknown isoform (PPARγ-PDL). PPARγ and PPARγ-UBI were predominantly expressed. CoIP-fctp revealed that PPARγ-UBI was selectively associated with NF-κB p65, a key transcriptional factor of IL-6 expression. PB2 suppressed LPS-induced-IL-6 expression exacerbated by the over-expression of PPARγ-UBI. In the murine periodontitis model, topical application of PB2 significantly mitigated alveolar bone loss. Conclusion: These results suggest that the anti-inflammatory effects of PB2 in periodontal tissues/cells are distinct, and these effects arise from the inhibition of PPARγ-UBI; hence, the application of PB2 and modification of the splicing event in three PPARγ isoforms have therapeutic potential for preventing periodontitis.